Impact of Overexcitation Limiters on the Power System Stability Margin Under Stressed Conditions - Anagnostou,G; Pal,BC (IEEE Transactions on Power Systems, 2015)
This paper investigates the impact of the overexcitation limiters (OELs) on the stability margin of a power system which is operating under stressed conditions. Several OEL modeling approaches are presented and the effect of their action has been examined in model power systems. It is realized that, more often than not, OEL operating status goes undetected by existing dynamic security assessment tools commonly used in the industry. It is found that the identification and accurate representation of OELs lead to significantly different transient stability margins. Unscented Kalman filtering is used to detect the OEL activation events. In the context of stressed system operation, such quantitative assessment is very useful for system control. This understanding is further reinforced through detailed studies in two model power systems.